A modified hand washing method for resource limited settings - Sarwar, Samreen; Muhammad, Javed; Shahzad, Faheem (Frontiers in Public Health, 2022)
The Good Microbiological Practices & Procedures (GMPP) is the most significant risk control measure as per the fourth edition of the WHO laboratory biosafety manual. Among GMPP, one of the best practices is hand washing. WHO and other public health agencies have published several guidance documents on hand washing, that describe closing the tap using a disposable paper towel/tissue paper at the end of hand washing as one of the critical steps. In resource-limited settings, where disposable paper towels cannot be provided at all times, the staff is left with ambiguous instructions on how to close the tap. In this paper, a modified hand washing method is documented that doesn't necessitate the use of disposable paper towels. In this method, both hands and faucets remain in contact with soap for at least 40–60 s. The method was validated by the use of Glo Germ. A survey questionnaire was also designed and conducted for the lab staff (n = 12) of the two laboratories, where this method was implemented, to assess whether this hand washing method brought any improvement in their hand washing practices and implementation. All (100%) of the survey respondents reported that this method of hand washing is more applicable and implementable than the WHO-recommended hand washing technique. Eighty three percentage reported that this modified method of hand washing raised their hand washing compliance. The authors suggest that this hand washing method can be used in resource-limited laboratory settings as an effective GMPP to ensure infection control.